2021
DOI: 10.3390/diagnostics11040609
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Imaging of Abdominal Wall Endometriosis: A Pictorial Review

Abstract: Endometriosis is a debilitating disease characterized by endometrial glands and stroma outside the endometrial cavity. Abdominal wall endometriosis (AWE) indicates the presence of ectopic endometrium between the peritoneum and the skin, including subcutaneous adipose tissue and muscle layers, often following obstetric and gynecological surgical procedures. AWE is a not infrequent gynecological surgical complication, due to the increasing number of cesarean sections worldwide. In this pictorial review, we discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…A spherical umbilical nodule in the dermal-epidermal layer and hypodermis, solid with varied echogenicity, most typically hypoechoic with an anechoic cystic component, is seen on ultrasound [8] . The margins are smudged or spiculated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A spherical umbilical nodule in the dermal-epidermal layer and hypodermis, solid with varied echogenicity, most typically hypoechoic with an anechoic cystic component, is seen on ultrasound [8] . The margins are smudged or spiculated.…”
Section: Discussionmentioning
confidence: 99%
“…The margins are smudged or spiculated. Color Doppler can be used to detect intralesional vascular patches in some cases [8] .…”
Section: Discussionmentioning
confidence: 99%
“…17B) are common differential diagnoses for palpable inguinal masses. Endometriosis (presence of endometrial tissue outside the uterus) can manifest as a palpable mass in the inguinal region [19] but is rare. Such extra-pelvic endometrial tissues can be found in the cutaneous, subcutaneous, and intramuscular layers.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Inguinal hernias are classified as direct and indirect based on the relationship of the herniation sac with the inguinal canal [ 1 ], while both types can involve structures from the intraperitoneal or extraperitoneal space [ 2 ]. A direct hernia is formed when the hernia sac protrudes directly through the posterior wall of the inguinal canal [ 3 , 4 ], while in the indirect type, the sac follows the inguinal canal in conjunction with the spermatic cord after entering through the internal inguinal ring [ 5 , 6 ]. The prevalence of inguinal hernias accounts for 1.7% of the general population, with an increasing 4% in people older than 45 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%